Molecular Epidemiology of Carbapenem-Resistant Acinetobacter baumannii From Khartoum State, Sudan - Al-Hassan, Leena; Elbadawi, Hana; Osman, Einas; Ali, Sara; Elhag, Kamal; Cantillon, Daire; Wille, Julia; Seifert, Harald; Higgins, Paul G. (Frontiers in Microbiology, 2021)
Acinetobacter baumannii is an important global pathogen contributing to increased morbidity and mortality in hospitalized patients, particularly when infected with carbapenem resistant isolates, due to limited alternative treatment options. Nine international clonal (IC) lineages have been identified in many countries worldwide, however data still lacks from some parts of the world, particularly in Africa. We hereby present the molecular epidemiology of MDR A. baumannii from four hospitals in Khartoum, Sudan, collected from 2017-2018. Forty-two isolates were whole-genome sequenced, and subsequent molecular epidemiology was determined by core genome MLST (cgMLST), and their resistomes identified. All isolates had an array of diverse antibiotic resistance mechanisms conferring resistance to multiple classes of antibiotics. We found a predominance (88%) of IC2 (with the intrinsic OXA-66 and acquired OXA-23), and some with NDM-1. IC2 isolates were sub-divided into 4 STs separated by 5 to 431 allelic differences, and with evidence of seven transmission clusters. Isolates belonging to IC1, IC5 and IC9 were also identified. These data illustrate that MDR IC2 A. baumannii are widely distributed in Khartoum hospitals and are in possession of multiple antibiotic resistance determinants.